Continuous-flow phosphate removal using Cry-Ca-COS Monolith: Insights from dynamic adsorption modeling - Chanadda Phawachalotorn; Worawit Wongniramaikul; Satabodee Kaewnoo; Aree Choodum (Water Research X, 2024)
² = 0.9994 in the Yoon-Nelson model). An analysis of comprehensive errors was also conducted to assess the adequacy and precision of the model equations.
Keywords: Phosphorus and nutrient management; Minerals Flotation and Separation Techniques; Materials Engineering and Processing